Pengaruh Durasi Pengambilan Bagasi dan Citra Maskapai terhadap Kepuasan Penumpang di Bandar Udara Internasional Halim Perdanakusuma Jakarta - Yulyanah Turizkiyah; Nur Makkie Perdana Kusuma (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
In aviation, two important factors can affect passenger satisfaction: time efficiency in service, especially in the baggage claim process, and airline image. These two activities also apply to passengers at Halim Perdanakusuma International Airport. This study aims to determine whether there is an influence between the duration of baggage claim and airline image on passenger satisfaction, both partially and simultaneously. This study uses a quantitative approach to data collection. It distributes questionnaires to 105 Citilink Indonesia passengers and 105 Batik Air passengers who claim their baggage in the arrivals area. In addition, it uses baggage manifest data in the form of first baggage (fi-bag) and last baggage (la-bag) time data. The data is then analyzed using the t-test (partial test) and f-test (simultaneous test). The results of the study indicate that partially, the Baggage Claim Duration variable has a significant effect on the Passenger Satisfaction variable, both for Citilink Airlines (sig.=0.30) and Batik Air (sig.0.035). The results of the study indicate that partially, the Airline Image variable has a significant effect on the Passenger Satisfaction variable for both Citilink Airlines (sig.=0.000) and Batik Air (sig.=0.000). Furthermore, the Baggage Claim Duration and Airline Image variables simultaneously affect the Passenger Satisfaction variable, with a significance of 0.000 for both Citilink and Batik Air Airlines.